Impact of different size training curricula on young football's physiological variables (Global Scientific Review, 2024)
The game of football is one of the games that has received increasing global attention as the most popular in the world, which made specialists always seek to develop the game by raising the levels of players in various aspects of preparation. And that this interest and integration between the numbers of skills, plans and physical came as a result of sound scientific planning for the training stages, which also leads to improved performance, and the research acquires its importance by identifying the impact of training curricula of different sizes in football for junior teams. The study aimed to identify the impact of training curricula of different sizes in physiological variables, and to stand on one of the important training aspects because of its positive impact on the player's performance during the match and to know the results of the study, which helps in directing the process of preparing young players according to scientific foundations, and the problem of research was to conduct one training unit per day for juniors during the training curricula and are almost equal sizes and with one training rhythm during one training unit In order to develop the physical and skill aspect. The researcher used the experimental approach by designing the experimental and control groups, and concluded through it a clear development of the experimental group, which trained by two training units per day better than the control group, which was trained by one training per day. There were also no significant differences in the blood pressure variable before and after exertion